Treatment of in fatty liver with L-carnitine - Bahcecioglu, I.H.; Celebi, S.; Akfirat, M.; Cihangiroglu, M.; Donder, E. (My University, 1998)
One of the mechanisms of fatty liver is impairment of mitochondrial ? oxidation of fatty acids. Mitochondrial ? oxidation of long chain fatty acids depends on the availability of carnitine. In this study, we investigated the effects of L-carnitine in patients with fatty liver diagnosed by ultrasonography and tomography. Twenty patients in treatment group were given L-carnitine 2 g/day and nine patients in the control group were given a multivitamin for a trial period of two months. After treatment, the levels of ALT and AST were significantly reduced in the L-carnitine group (p<0.05). There was no difference in echogeneities between the two groups on ultrasonography. Treatment with L-carnitine appears to be effective in patients with fatty liver. The possible benefit of L-carnitine therapy should be investigated further in the context of randomized, controlled trials.
Yagli karacigerde L-karnitin tedavisi
Keywords: Fatty liver; L-carnitine